Penanaman Karakter Disiplin Melalui Metode Keteladanan - Salsabilla, Mahila; Muhammad Ariffudin (FATAWA: Jurnal Pendidikan Agama Islam, 2022)
This study aims to describe how to instill disciplinary character through exemplary methods in students of SMP Al-Azhar Menganti Gresik, to identify what are the supporting factors and what are the inhibiting factors in instilling disciplinary character through exemplary methods in students of SMP Al-Azhar Menganti Gresik. In this study using a qualitative approach. Data were collected through observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and conclusion. The results of the research on instilling disciplinary character through exemplary methods in SMP Al-Azhar Menganti Gresik include, 1) In instilling disciplinary character that the average teacher attendance is 80%, it has shown good results and it all starts with the teacher himself and the teacher is directly involved in the environment as a role model. The forms applied by the teacher through exemplary methods are time discipline, uniform discipline, and discipline in obeying rules. The purpose of forming a disciplinary character is so that children can understand the rules that apply in school as things that must be obeyed. Furthermore, if there are students who violate school discipline, the school will provide sanctions aimed at giving a deterrent effect to these students but not violating the norms of religious education, still providing examples of a good education. 2) Supporting factors: student self-awareness, the existence of teacher cooperation, the role of the teacher, and the role of parents. 3) Inhibiting factors: lack of awareness in students, family factors, environmental factors, or student association.